Improving The Quality Of Local Government Financial Reporting Through The Impact Of Internal Control System With Human Resource Competencies As A Moderator - Mutoharoh Mutoharoh; Luluk Muhimatul Ifada (Universitas Muhammadiyah Malang, 2023)
Purpose: The increasing demand for transparency and accountability of the government institutions has led to an interesting discussion about the factors that affect the quality of government financial reports. This study examines the effect of the internal control system on the financial reports quality at Kudus Regency government agencies by raising human resource competency as a moderating variable. Methodology/approach: Questionnaires were distributed to all local government institutions and as many as 106 answers were returned for processing. Analysis using Partial least Square (PLS) for hypothesis testing. Findings: The results prove that the internal control system has a positive effect on the financial reports quality. However, in terms of moderating effect, human resource competence in fact, weakens the influence of the internal control system on the quality of financial reports. Practical implications: By highlighting best practices from local government institutions, the results of this research are expected to become relevant considerations in determining strategy to improve local government services. Originality/value: This study raises the case of best practice in the Kudus Regency Government, which in 2022 received an Unqualified Opinion from the Indonesian Audit Board on their Regional Government Financial Report for the 2021 fiscal year. The Unqualified opinion in Kudus Regency is the tenth consecutive achievement, making this research interesting and has become a model for other local governments.